2012
DOI: 10.1371/journal.pone.0051619
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Characterization, and Cellular Localization of Knowpains, Papain-Like Cysteine Proteases of the Plasmodium knowlesi Malaria Parasite

Abstract: Papain-like cysteine proteases of malaria parasites degrade haemoglobin in an acidic food vacuole to provide amino acids for intraerythrocytic parasites. These proteases are potential drug targets because their inhibitors block parasite development, and efforts are underway to develop chemotherapeutic inhibitors of these proteases as the treatments for malaria. Plasmodium knowlesi has recently been shown to be an important human pathogen in parts of Asia. We report expression and characterization of three P. k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In T. parva they are thought to facilitate lymphocyte invasion [ 16 ]. Papain family cysteine proteases have been considered as potential vaccine targets in the related apicomplexan Plasmodium falciparum [ 17 ], and the previously described T. parva antigen Tp8, in chromosome 2 (TpMuguga_02g00140), is a papain family cysteine protease. The polymorphic papain cysteine protease identified here (TpMuguga_03g00280) is located in chromosome 3, and its antigenic potential warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In T. parva they are thought to facilitate lymphocyte invasion [ 16 ]. Papain family cysteine proteases have been considered as potential vaccine targets in the related apicomplexan Plasmodium falciparum [ 17 ], and the previously described T. parva antigen Tp8, in chromosome 2 (TpMuguga_02g00140), is a papain family cysteine protease. The polymorphic papain cysteine protease identified here (TpMuguga_03g00280) is located in chromosome 3, and its antigenic potential warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…DTT was found to enhance enzyme activities of knowpains (Prasad et al 2012), Falcipain-2 (Sarduy et al 2012, DerF1 and DerP1 (Takai et al 2002) in a dose-dependent manner. Different pH buffers also showed significant effects on cathepsin F-like cysteine protease (Joo et al 2007), knowpains (Prasad et al 2012), Tr-cp 14 (Asp et al 2004) and Falcipain-2 (Sarduy et al 2012) activities; the maximum activities often obtained in acidic pH. The concentration of cysteine protease used in enzyme activity assays is between 0.1 and 10 nM (Bromme et al 2004).…”
Section: Cysteine Proteases Activation and Enzyme Activity Examinationmentioning
confidence: 96%
“…The buffer, DTT and EDTA concentrations vary between protocols, and their effect on the enzyme activities was in controversy. Some researchs deemed that these factors don't have a significant effect on the enzyme activities (Bromme et al 2004;Joo et al 2007;Prasad et al 2012). However, some other literatures showed different perspectives.…”
Section: Cysteine Proteases Activation and Enzyme Activity Examinationmentioning
confidence: 99%
“…Also, KP-4 was observed to have essential role in erythrocyte cytoskeleton breakdown facilitating merozoite egress. Accordingly, the investigators suggested using in vitro culture of P. knowlesi for searching a VP specific inhibitor in the absence of an efficient in vitro culture system for P. vivax [58] .…”
Section: Homologs and Orthologsmentioning
confidence: 99%